1999
DOI: 10.1002/(sici)1097-0223(199912)19:13<1242::aid-pd736>3.0.co;2-p
|View full text |Cite
|
Sign up to set email alerts
|

Confirmation of diagnosis in preimplantation genetic diagnosis (PGD) through blastocyst culture: preliminary experience

Abstract: Three cases of preimplantation genetic diagnosis (PGD) (two for sexing and one for aneuploidy screening) are presented. Embryo biopsy was performed at day 3 and diagnosis was established with fluorescent in situ hybridization (FISH). Embryos not used for replacement were cultured in sequential media for blastocyst development. Blastocyst rate was 39.3 per cent. Confirmations of diagnosis were established with FISH in blastocysts and arrested embryos. Mosaicism was observed in 7/8 blastocysts (mean number of ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
9
0

Year Published

1999
1999
2014
2014

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 43 publications
(10 citation statements)
references
References 36 publications
1
9
0
Order By: Relevance
“…Previous reports have implicated mosaicism as a source of discordance among blastormeres and have suggested that mosaicism is the major drawback in the efficiency and reliability of preimplantation genetic diagnosis [17,18]. Chromosomally abnormal cells can coexist with normal cells and mosaic embryos can develop to morphologically [27] and chromosomally [20] normal blastocysts in vitro.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous reports have implicated mosaicism as a source of discordance among blastormeres and have suggested that mosaicism is the major drawback in the efficiency and reliability of preimplantation genetic diagnosis [17,18]. Chromosomally abnormal cells can coexist with normal cells and mosaic embryos can develop to morphologically [27] and chromosomally [20] normal blastocysts in vitro.…”
Section: Discussionmentioning
confidence: 99%
“…A major pitfall of PGD for aneuploidy screening with a single blastomere biopsy is the existence of mosaicism [17][18][19][20][21]. Chromosomally normal and abnormal blastomeres can coexist within the same early-cleavage-stage embryo [19].…”
Section: Introductionmentioning
confidence: 89%
See 1 more Smart Citation
“…As the blastomeres divide and the embryos develop to the blastocyst stage, diploidYpolyploid mosaicism appears more frequently (Bielanska et al 2002). DiploidY tetraploid mosaicism was noted in 3Y26% of early morula stage human IVP embryos while the figure reached 23Y74% in blastocysts (Veiga et al 1999, Ruangvutilert et al 2000. Our observation on sheep embryos is comparable to those on human embryos (Veiga et al 1999, Ruangvutilert et al 2000.…”
Section: Discussionmentioning
confidence: 99%
“…As such, the biopsy of 6 to 10 cells from the outer layer of the trophectoderm is less likely to have a detrimental effect on the blastocyst's mass of the developing fetus which originates from the inner cell mass (ICM). 282,283,291 The technique of zona slitting (similar to partial zona dissection) can be used to open the zona pellucida with a microneedle. 282 The blastocyst zona can also be opened using a laser.…”
Section: Trophectoderm Biopsymentioning
confidence: 67%